All‐cause and suicide mortality among people with methamphetamine use disorder: a nation‐wide cohort study in Taiwan - Lee, Wan‐Chen; Chang, Hu‐Ming; Huang, Ming‐Chyi; Pan, Chun‐Hung; Su, Sheng‐Siang; Tsai, Shang‐Ying; Chen, Chiao‐Chicy; Kuo, Chian‐Jue (Addiction (Abingdon, England), 2021)
Background and aims Although methamphetamine use is a serious public health problem, large‐scale cohort studies assessing methamphetamine‐related mortality are scant. This study investigated all‐cause mortality and suicide methods in people with methamphetamine use disorder. Design A cohort record‐linkage study using data from Taiwan's National Health Research Institute Database (NHIRD) linked to Taiwan's National Death Certification System. Setting Taiwan. Participants A total of 23 248 individuals with methamphetamine use disorder between 1 January 2001 and 31 December 2005. Measurements The outcome variables included mortality rates and standardized mortality ratios (SMRs) for all causes of death and for each suicide method. Findings Compared with the general population, the current cohort had an increased all‐cause mortality (SMR = 5.4), with the SMR for unnatural causes (14.8) higher than that for natural causes (7.5). Among all causes of death, suicide had the highest SMR (16.3), followed by neurological diseases (9.7). Among the methods of choice for suicide, drug overdose had the highest SMR (24.9). The incidence of charcoal burning and hanging was significantly higher in men and that of jumping from a high place was significantly higher in women. Conclusion People in Taiwan with methamphetamine use disorder appear to have a significantly increased all‐cause mortality rate compared with the general population, with suicide having the highest contribution, particularly suicide via drug overdose. The methods of choice for suicide revealed distinct patterns between men and women.